Schiff Base in Organic, Inorganic and Physical Chemistry - Akitsu, Takashiro (IntechOpen, 2023)
A Schiff base (imine -N=CH-) is a part of a popular group of organic compounds prepared form primary amines and aldehyde. Many studies have been carried out on Schiff bases not only as organic compounds but also as ligands for metal complexes. In this context, this book provides a comprehensive, interdisciplinary review of Schiff base compounds, with an emphasis on the latest advances. It compiles research results, commentary, reviews, and more dealing with preparation, spectroscopy, crystallography, (asymmetric) synthetic roles, physical properties (magnets, optics, etc.), computational chemistry, and theoretical chemistry. The book focuses on Schiff base and its strong connection to organic chemistry, biochemistry, and polymer materials chemistry. It covers three topics: Schiff base of organic chemistry, Schiff base of inorganic chemistry, and Schiff base of functional or biological materials.